PKM BUDIDAYA & PENGOLAHAN MAGOT SEBAGAI SOLUSI GREEN ECONOMY RANGKA REVITALISASI SAVE MANINJAU - Susanti, Dessi; Irianto, Agus; Lestari, Tuti; LV, Yuhendri; Syofyan, Rita; Armiati, Armiati; Rahmidani, Rose (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Maju Bersama Mandiri Fishermen's Group Galapung Tanjung Sani, Tanjung Raya, Agam Regency is unable to: 1) Carry out magot cultivation to improve the family's economy as well as an effort to reduce the amount of waste, 2) Carry out magot processing as an alternative fish feed in order to increase family economy. Based on the urgent needs of the Maju Bersama Mandiri Fishermen's Group Galapung Tanjung Sani, Tanjung Raya, Agam Regency, for them Lake Maninjau is the main source of livelihood and economy for their families (Lake Maninjau is one of the critical lakes which is a super priority lake to be saved through the government's revitalization program ). So the solution offered to solve the problem of the Maju Bersama Mandiri Fishermen's Group Galapung Tanjung Sani, Tanjung Raya, Agam Regency is: 1) Workshop and assistance in magot cultivation as a green economy solution in the context of revitalizing save maninjau, 2) Workshop and assistance in processing magot into alternative fish food as a green economy solution in the context of revitalizing save maninjau The targets to be achieved through this PKM activity are as follows: 1) 20 fishermen who are members of Maju Bersama Mandiri Fishermen's Group Galapung Tanjung Sani, Tanjung Raya, Agam Regency are able to carry out magot cultivation as a green economy solution in the context of revitalizing save maninjau, 2) 20 fishermen who are members of Maju Bersama Mandiri Fishermen's Group Galapung Tanjung Sani, Tanjung Raya, Agam Regency are able to process magot into alternative fish food as a green economy solution in the context of revitalizing save maninjau.